The Learning Model of Forearm Passing In Volleyball for Junior High School - Titi Ajayati (STKIP Singkawang, 2017)
The purpose of this research and development is to produce the learning models of volleyball forearm for junior high school age. In addition, research and development are conducted to Obtain in-depth information about the development and application of the learning models of volleyball forearm for junior high school age and Determine the effectiveness, efficiency, and attractiveness of the models created a child. This research uses methods development research & development (R & D) from Borg and Gall. Subjects in research and development are the students of junior high school consisting of 35 children. The Instruments that used in this research and development is a questionnaire, as well as the instrument volleyball passing a test that used to collect data of the forearm passing in volleyball for junior high school age. As for the stages in research and development are (1) analysis of needs, (2) the expert evaluation (initial product evaluation); (3) limited trial (small group testing); and (4) the main trial (field testing). The effectiveness model of test used forearm passing to know the level of forearm passing ability for junior high school age before giving treatment such as forearm passing models that developed and to Determine the forearm passing ability after treatment or forearm passing treatment that developed, from the initial tests were conducted obtained the student forearm passing levels are 21.06, then after being given treatment in the form of forearm passing model. The students’ forearm passing skils obtained the ability levels are 26.26. Accordingly, this volleyball forearm passing model is effective to raise the learning models of forearm passing in volleyball for junior high school age. Based on the results of the development can be concluded that: (1) the forearm passing in volleyball learning models for junior high school age can be developed and applied in physical education learning at schools (2) the forearm passing in volleyball learning models for junior high school age the which have been developed, acquired improvement evidence of this is shown in the result of testing the data from the pretest and posttest there is significant difference between before and after the development of a models.